WorldFlora: An R package for exact and fuzzy matching of plant names against the World Flora Online taxonomic backbone data. (25th September 2020) - Kindt, Roeland
Abstract : Premise: The standardization of plant names is a critical step in various fields of biology, including biodiversity, biogeography, and vegetation research. The WorldFlora package is introduced here to help achieve this goal by matching lists of plant names with a static copy from World Flora Online (WFO), an ongoing global effort to complete an online flora of all known vascular plants and bryophytes by 2020. Methods and Results: Based on direct and fuzzy matching, WorldFlora inserts matching cases from the WFO to a submitted data set containing taxonomic names. The results and success rates for selecting the expected best single matches are presented for four data sets, including two data sets used in recent comparisons of software tools for correcting taxon names. Conclusions: WorldFlora offers a straightforward pipeline for semi‐automatic plant name checking. For the four data sets, the success rate of credible matches ranged from 94.7% to 99.9%.